Electrical Transport Properties of (Bi1.6Pb0.4Sr2Ca2Cu3O10)/Ag Tapes with Different Nanosized MgO - Nabil A. A. Yahya; R. Abd-Shukor (Advances in Condensed Matter Physics)
MgO nanopowders with average size 20 and 40 nm were introduced into (Bi1.6Pb0.4Sr2Ca2Cu3O10)(MgO)x (x=0–0.15 wt.%) in the pellet form. The optimum amounts for the highest transport critical current density Jc were x=0.10 and 0.01 wt.% for 20 and 40 nm MgO, respectively. These results were used to fabricate MgO added (Bi, Pb)-2223/Ag sheathed tapes using the powder-in-tube method. The tapes were sintered at 845°C for 50 h and 100 h. The structure, microstructure, and Jc of the tapes were determined. The temperature and magnetic field dependence of Jc for the MgO added tapes exhibited a significant enhancement compared with the nonadded tapes. Jc of 20 nm MgO added tape was higher compared with the 40 nm MgO added tape. A higher Jc was obtained when the tapes were sintered for 100 h. The increase in Jc can be explained as the increase of the flux pinning strength by nanosized MgO. The nanoparticle with size closer to the coherence length was more effective in enhancing Jc.